PERILAKU MENYIMPANG DIKALANGAN MAHASISWA PEKANBARU (Studi Kasus Pola Berpacaran Pada Mahasiswa Di Kost Kelurahan Air Dingin) - Piliang, Rama Irwandy; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Deviant behavior is always present in society. Dating has become a familiar phenomenon in the community. Students are adolescents who will grow up and begin to recognize love always expressing feelings through a bond of dating, but what happens if in dating they have sex that should be done by a married couple. The boarding house which is supposed to be a place of refuge when away from family while attending education is abused by students is a place to date Deviant behavior is always present in the community. Dating has become a familiar phenomenon in the community. Students are adolescents who will grow up and begin to recognize love always expressing feelings through a bond of dating, but what happens if in dating they have sex that should be done by a married couple. The boarding house which is supposed to be a place of refuge when away from family while attending education is abused by students is a place for dating. Existing free sex conducted by boarding students is a deviant behavior from the norms that exist in the community. This study aims to determine the sexual behavior of students in dating in boarding, starting from the story of their initial introduction to deciding to date, what activities during dating to how sexual behavior in dating occurs, and what are the factors that cause a person to engage in sexual behavior. dating is boarded. The theory used in this study is the theory of social deviation. This research is included in qualitative approach and descriptive type, data collection using in-depth interview, observation and documentation methods. The results of the study explained that the background that caused free sex occurred was through mass media and electronic media which were able to change students' thinking patterns, the influence of peers who became socialization agents after parents. Lack of control and visit by parents, then there is no direct supervision from boarding house owners and people who do not care.Keywords: Student, Sexual Behavior, Boarding House